Antibacterial Activity of Some Commonly Used Food Commodities Against Escherichia coli, Salmonella typhi and Staphylococcus aureus: Antibacterial Activity of Food - Khan, Seema Ismat; Siddiqui, Anila; Ansari, Asma (Biological Sciences - PJSIR, 2009)
The activity of commonly used spices and salt, sugar and pickles against Escherichia coli, Salmonella typhi, and Staphylococcus aureus was tested. The antibacterial activity was found to be in descending order like coriander>pickles>salt and sugar>clove>turmeric>black pepper>red chilli against S. typhi and garlic>clove>onion>ginger against S. aureus.